Channelling medical truths from Sir William Osler. Issue 11 (1st November 2018) - Isbister, James P.
Abstract: Dr James L. T. Isbister (JLT), a graduate of the University of Adelaide, came to Sydney as a clinical pathologist at Sydney Hospital in 1897 and subsequently was a general practitioner in North Sydney and honorary surgeon and gynaecologist at Royal North Shore Hospital from 1900. He owned the first motor vehicle in North Sydney and he was Mary MacKillops's local doctor during her last years at the Sisters of St Joseph of the Sacred Heart convent in North Sydney. On a visit to the United Kingdom in 1908, he met Sir William Osler, a meeting that clearly impacted on his thinking that has been channelled down the Isbister medical family for over a century. JLT was a founding member of the Royal Australasian College of Surgeons with a grandson, Peter, also becoming a fellow. His son, James, daughter‐in‐law, Clair, and grandson, James, became fellows of the Royal Australasian College of Physicians. More recently, his great‐grand daughter is currently an advanced college trainee. In this historical perspective, JLT's grandson confirms that Osler's medical truths have been channelled, added to and practised by JLT and his descendants.